PENGARUH MEDIA PEMBELAJARAN BERBASIS INFORMASI TEKNOLOGI (IT) TERHADAP PRESTASI BELAJAR FIQIH SISWA DI MADRASAH IBTIDAIYAH - Iffah Mukhlisah (MAMBA'UL 'ULUM, 2019)
This study is intended to know: (1) the use of information technology (IT) Media (2) Fiqih achievement students. (3)The Interaction of the between learning media and Fiqih achievement. The method was used in this research is experiment method. The objets of this research are 40 students of Madrasah Ibtidaiyah in Sragen district that separated 20 students as experiment group, 20 students as control group. Data collecting method using questionnaire for the use of information technology (IT) media , interview, documentation, observation and tes for Fiqih achievement. Data analysis technique using Liliefors for normalitas test and y=a+bx for linier test. For correlation use product moment with significant 5%.Based the result of research shows that there is an interaction between the effect of information technology (IT) Media and achievement in Fiqih (Fab>Ftable or 0,866>0,444), it can therefor said that hypothesis was accepted.